Optimization of Household Waste Management in Manado City - Christianson Kapojos, Chandra; H. E. Sendouw, Recky; Rahman Dilapanga, Abdul (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Garbage in Indonesia is a serious problem that has social, economic and cultural impacts. Waste management in almost all cities in Indonesia is experiencing problems, mainly due to the lack of Final Processing Sites (TPA). As a result, people often throw garbage in rivers, ditches, rivers and the sea. With a population that is in the top 10 in the world, Indonesia's waste production reached 65 million tons in 2016. Garbage causes various problems in society, including natural disasters such as floods. The lack of public awareness in disposing of waste in the appropriate place, as well as the lack of selection and recycling of waste, has an impact on natural disasters and damaged environment. The government needs to learn from the experience of the disaster and take preventive steps. The responsibility for waste management lies not only with the community, but also with the local government. The government needs to regulate and inform the public about proper waste management, as well as provide facilities that assist in waste management. The scale of waste management is carried out through the collection, transfer, processing and transportation of waste to the TPA. With population growth and regional development, the amount of waste generated is increasing. To maintain environmental sustainability, it is necessary to limit and reduce waste generation. Waste can also be turned into a resource through recycling and reuse. Therefore, the government makes national policies and strategies as well as guidelines for local governments in managing household waste and the like. Manado City refers to Regional Regulation Number 1 of 2021 in waste management. However, the volume of waste in Manado City continues to increase along with the rapid population growth. Limited garbage collection vehicles have caused some waste to go unmanaged and accumulate in rivers, drainages and other places. Lack of trash bins, delays in transporting waste from TPS to TPA, and poor TPA management are also problems. Research shows that there are several violations in waste management in Manado, such as a lack of public awareness in disposing of waste, the minimum number of garbage collection fleets, and delays in waste transportation. Garbage is still scattered in various corners of the city, including the coast and rivers. TPA management is also not optimal, causing public health and hygiene to be disrupted. Public awareness to dispose of garbage at the specified time is still lacking. In order to overcome this problem, it is necessary to increase public awareness, improve waste collection facilities and fleets, and improve the effective management of landfills. With these steps, it is hoped that waste management in Indonesia, especially in Manado City, can reduce its negative impact and become more sustainable.